A Rare Case of Adductor Longus Muscle Rupture - van de Kimmenade, R. J. L. L. (Case Rep Orthop, 2015)
An adductor longus muscle rupture is a rare injury. This case report describes a 32-year-old patient with an adductor longus rupture. The trauma mechanism was a hyperabduction movement during a soccer game. Nonoperative treatment was initiated. After a follow-up of 4 years, the patient was without pain but a small swelling was still visible. This report describes the anatomy, pathophysiology, and evidence-based treatment of adductor longus rupture.